Kinetics and Mechanism of Ni/Zeolite-Catalyzed Hydrocracking of Palm Oil into Bio-Fuel - Sri Kadarwati; Fitri Rahmawati; Puji Eka Rahayu; Kasmadi Imam Supardi (Indonesian Journal of Chemistry, 2013)
Kinetics and mechanisms of Ni/zeolite-catalyzed cracking reaction of methyl ester palm oil (MEPO) were studied using a continuous flow-fixed bed reactor system at an atmospheric pressure. The catalyst was prepared by wet impregnation method with a solution of nickel nitrate hexahydrate as the precursor and zeolite as carrier. The characteristics of catalyst including active Ni metal content, crystallinity, total acidity, and porosity were evaluated. The reactions were performed with a varied hydrogen flow rate as a carrier gas as well as a reductant and reaction time. Liquid products were analyzed by GC. Analysis by GC-MS was only conducted on a product at hydrogen flow rate with the best conversion. It has been shown that the catalyst has a superior character for hydrocracking reactions of MEPO into green fuel. No considerable effect of hydrogen flow rate on the total conversion was observed. The tests showed that the kinetics of Ni/zeolite-catalyzed cracking reaction followed pseudo-first order kinetics. GC-MS analysis revealed the formation of light hydrocarbon products with C6-C8 of aliphatic and cyclic components without oxygenates. Distribution of the product indicated that the cracking reaction as well as the isomerization of the products of hydrocracking occurred. Thus, Ni/zeolite-catalyzed cracking involved cracking /hydrogenation, isomerization, cyclization, and deoxygenation.